Access to the Media – A Precondition for Critical Public - Turnšek Hančič, Maja (Javnost-The Public, 2009)
The article builds upon the normative concept of the public as a group of people who publicly and critically deliberate upon matters of common concern. Such a public deliberation should be characterised, fi rst, by openness to all who are potentially aff ected by the issue at hand, and second, by critical refl ection and oversight upon public authorities with the primary aim of providing social changes. The author analyses results of two research projects, Political Communication Cultures in Western Europe and Diversity and Political Orientation of Slovenian Daily Press, 1990-2005, in order to answer three main research questions: (1) what is the diversity of sources of attitudes expressed in the Slovenian daily newspapers and in readers’ letters to the editor, (2) what is the diversity of the users of new media, and (3) to what extent are citizens who are actively involved in public debate, critical of the political authorities and the operation of mass media in Slovenia?